Graves hyperthyroidism in pregnancy: a rare presentation - Garg, Priyanka; Bansal, Romi; ., Roushali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Hyperthyroidism in pregnancy is much less common occurring in 0.1-0.2% of women with Grave’s disease being the most common cause accounting for 90% of the cases. It is important to diagnose hyperthyroidism in pregnancy because fetal loss in untreated patients is high and may even be life threatening for the mother. We are presenting a case of 29 years old G3P2L1 who presented to our emergency with amenorrhea of 7 months and history of loose stools for the last 20 days. It was associated with generalized weakness. She also had history of palpitations, weight loss and sleep disturbances. She was a known case of hyperthyroidism for the past 1-2 years and was already taking anti-thyroid drugs. B/L exophthalmos was apparently present. Patient was severly anaemic with haemoglobin of 5.5gms/dl. Ultrasound showed fetal demise at 28weeks. Patient was given 3 units of blood transfusion and was induced with prostaglandins. She delivered a dead male baby weighing 1.2kgs. Her postpartum period was uneventful. Timely diagnosis of graves hyperthyroidism and its optimal treatment throughout pregnancy is vital in reducing maternal, fetal and neonatal complications.